2012
DOI: 10.1080/09766634.2012.11885561
|View full text |Cite
|
Sign up to set email alerts
|

Availability and Adequacy of Human and Material Resources for the Teaching and Learning of Skill-based Courses in Nigeria Public Universities

Abstract: This study was carried out to access the availability and adequacy of human and material resources for the teaching and learning of skill-based courses in Nigerian Public Universities. In doing this, three (3) research questions and two (2) hypotheses were formulated. The population of this study consisted of academic staff and final year students of 2009/2010 academic session in Nigerian Public Universities. The instruments used to collect data were the questionnaire and checklist. The researcher personally v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 1 publication
0
5
0
Order By: Relevance
“…Many authors argued that the inadequacy of physical facilities negatively affect teaching and learning processes in TVET institutions (Mupinga, Busby, & Ngatiah, 2006;Ayuba & Gatabazi, 2010;Indoshi, Wagah, & Agak, 2010;Hooker et al, 2011;Akinfolarin, Ajayi & Oloruntegbe, 2012;Aworanti, 2015). Osarenren-Osaghae & Irabor (2012) observed that in most TVET institutions, the state of physical facilities is such that cannot permit the stimulation of effective teaching and learning processes. More so, the utilization of outdated facilities negatively predicts the teaching and learning effectiveness in TVET (UNESCO, 2010).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Many authors argued that the inadequacy of physical facilities negatively affect teaching and learning processes in TVET institutions (Mupinga, Busby, & Ngatiah, 2006;Ayuba & Gatabazi, 2010;Indoshi, Wagah, & Agak, 2010;Hooker et al, 2011;Akinfolarin, Ajayi & Oloruntegbe, 2012;Aworanti, 2015). Osarenren-Osaghae & Irabor (2012) observed that in most TVET institutions, the state of physical facilities is such that cannot permit the stimulation of effective teaching and learning processes. More so, the utilization of outdated facilities negatively predicts the teaching and learning effectiveness in TVET (UNESCO, 2010).…”
Section: Literature Reviewmentioning
confidence: 99%
“…A review of the literature, as exemplified above, simply reveals that many authors (i.e. Yara & Otieno, 2010;Owoeye & Yara, 2011;Moochi, 2012;Osarenren-Osaghae & Irabor, 2012;Oguntuase, Awe & Ajayi, 2013) have investigated the influence of resource adequacy and utilization on curriculum implementation. However, none of these authors and researchers, nor more current investigations (Chukwunwendu, 2015;Munguti, 2016;Omae, et al, 2016;Chepkonga, 2017;Kigwilu & Akala, 2017;Ubulom & Ogwunte, 2017;Dhakal, 2017;Mutindi, 2018) on curriculum implementation specifically assessed the level of resource adequacy and utilization for teaching and learning effectiveness in TVET programs.…”
Section: Literature Reviewmentioning
confidence: 99%
“…A review of the literature, as exemplified above, simply reveals that many authors (such as, Yara & Otieno, 2010;Owoeye & Yara, 2011;Moochi, 2012;Osarenren-Osaghae & Irabor, 2012;Oguntuase, Awe & Ajayi, 2013) have investigated the influence of resource adequacy and utilization on curriculum implementation. However, none of these authors and researchers, nor more current investigations (Chukwunwendu, 2015;Munguti, 2016;Omae, et al, 2016;Chepkonga, 2017;Kigwilu & Akala, 2017;Ubulom & Ogwunte, 2017;Dhakal, 2017;Mutindi, 2018) on curriculum implementation specifically assessed the level of resource adequacy and utilization for teaching and learning effectiveness in TVET programmes.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This work went searching for the cause(s) of the problem, two important factors to the success of any form of education came to mind, and these were human and material resources, available for teaching and learning in the universities. Several studies have actually been carried out about these two factors in the past including the one by Osarenren-Osaghae [3] reading habits, proprietors' nonimplementation of agreements reached between them and staff, proprietors incessant interferences in the day to day running of the schools. These factors were also looked at because they also brought concerns to the universities.…”
Section: Historical Background Of Nigerian Public Universitiesmentioning
confidence: 99%
“…These findings did not come as a surprise, as an academic staff for over seventeen years in one of the universities in Nigeria, a lot of observations have attested to this fact. This study is in support of [3], which sought to know the availability and adequacy of the human and material resources for teaching and learning of skilled-based courses in Nigerian universities, where 10 public universities across the nation were picked by random sampling. Students and academic staff participated in this study, to guide the study, three research questions were asked and two hypotheses were formulated.…”
Section: Historical Background Of Nigerian Public Universitiesmentioning
confidence: 99%